The Propensity of Pentatricopeptide Repeat Genes to Evolve into Restorers of Cytoplasmic Male Sterility - Gaborieau, Lydiane; Brown, Gregory G.; Mireau, Hakim (Frontiers in Plant Science, 2016)
Cytoplasmic male sterility (CMS) is a widespread phenotype in plants, which present a defect in the production of functional pollen. The male sterilizing factors usually consist of unusual genes or open reading frames (ORFs) encoded by the mitochondrial genome. CMS can be suppressed by specific nuclear genes called restorers of fertility (Rfs). In the majority of cases, Rf genes produce proteins that act directly on the CMS conferring mitochondrial transcripts by binding them specifically and promoting processing events. In this review, we explore the wide array of mechanisms guiding fertility restoration. PPR proteins represent the most frequent protein class among identified Rfs and they exhibit ideal characteristics to evolve into restorer of fertility when the mechanism of restoration implies a post-transcriptional action. Here, we review the literature that highlights those characteristics and help explain why PPR proteins are ideal for the roles they play as restorers of fertility.